PREDICTIVE FACTORS FOR LOSS OF RESPONSE TO ANTI-TNF IN CROHN’S DISEASE - SANTOS,Byanca Rossetti Moreira dos (2020)
ABSTRACT Background: Anti-TNF drugs are a fundamental part of the treatment of Crohn’s disease (CD), so identifying factors related to loss of response is of great importance in clinical practice. Aim: Identify potential factors related to loss of response to anti-TNF agents in Crohn’s disease patients. Methods: This is a prospective study of CD patients attending a specialized outpatient clinic using a specific form, including patients with more than one year of follow-up on anti-TNF (Infliximab, Adalimumab or Certolizumab pegol). The information obtained was tabulated and analyzed to identify possible reasons for the loss of response to anti-TNF agents; results were submitted to statistical analysis by chi-square teste considering significant p<0.05. Results: Sixty-four patients were included, most of them females (56.3%), predominant age group between 26 and 55 years, of whom 25 required optimization, 23 remained in remission with the usual dose and interval, and 16 required switch; most of those who needed switch had hematological problems such as anemia and/or had already undergone surgical treatment for CD. Conclusions: Anemia and prior CD surgery have been linked to loss of anti-TNF response.